The Effect of Product, Word of Mouth, Location, and Price on the Decision to Choose the School of Economics and Business (STIEB) 'Perdana Mandiri' and Its Implications for Student Satisfaction - kristin Lukitaningrum; Sri Isti Untari; Anita Rahmawati; Rahma Nurpratiwi; Tika Dwi Ariyanti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
The decision to purchase or choose is a process in which consumers make a choice from various alternatives available, selecting the product that best fits their needs. Product quality, including performance, durability, and suitability, plays a significant role in this decision. In the context of higher education, product quality encompasses the study programs offered, innovations, and the added value provided to consumers, in this case, the students. STIEB